The features of reproductive health in women with multiple sclerosis - O. A. Tikhonovskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Introduction. The incidence of multiple sclerosis (MS) is two times higher in women, and the debut of the disease falls on young reproductive age, which makes the problem urgent. Purpose: to assess the characteristics of the reproductive health of women with MS in different age periods. Material and methods. A prospective study was carried out in parallel groups and a case-control study of women of early and late reproductive age with a reliable diagnosis of MS. Results. During pregnancy, there was a significant decrease in the frequency of exacerbations of MS in comparison with the pre-gravity period; voluntary infertility and childlessness is registered in 21.3 % and 32 % of women, respectively. An increase in the concentration of follicle stimulating hormone (FSH) means an increase in the degree of disability on the Expanded Disability Status Scale (EDSS) and the duration of the disease. The decrease in the concentration of dehydroepiandrosterone sulfate (DHEA-S) corresponds to a higher degree of disability on the EDSS scale and the duration of the disease. Conclusion. Pregnancy has a protective effect on the clinical course of MS. Infertility in most cases is voluntary, but at the same time hypergonadotropic condition and hypoandrogenia are observed in women with MS already in the early reproductive age, which interferes with the steroid synthetic function of the ovaries and can cause impaired fertility.